Classification of the aesthetics formula and generating the screen designs for balance principle - Ismail, Nor Anita Fairos (2002)
An important aspect of screen design is aesthetic evaluation of screen layouts. Screen designs aesthetic plays a greater role in Human-Computer Interaction (HCI). It is important to understand what characteristics of screens that influence user acceptance. Therefore, we required tools and principles for evaluating aesthetic of screen designs. However, no one knows how to measure aesthetic value of screen designs accurately. Ngo et. al.'s [D. C. L. Ngo et al, 1998-2001] has been proposed an interface aesthetics evaluation model and derived fourteen aesthetical measures for graphical screen design: Balance, Equilibrium Symmetry, Sequence, Cohesion, Unity, Proportion, Simplicity, Density, Regularity, Economy, Homogeneity, Rhythm, Order and Complexity. Based on the related work in field of screen design aesthetic, we were classified these fourteen aesthetic characteristics into three basic principles design in screen appearance (screen aesthetic): Balance, Unity and Movement. The end of this study, we transfer the mathematical theory for balance principle into a screen layout. The reason we carried out this study is there are none classification on aesthetic characteristic of screen design has been done before.